THE EFFECT OF GUIDED INQUIRY LEARNING MODELS ASSISTED BY ANIMATION MEDIA TOWARD STUDENTS LEARNING OUTCOMES - Salsabila, Putri; Muhiddin, Nurhayani H.; Arsyad, Arie Arma (Universitas Negeri Makassar, 2024)
The research aims to determine: 1) The level of student learning outcomes before and after implementation the guided inquiry learning model assisted by animation media and assisted by PPT media, 2) The improvement in student learning outcomes using guided inquiry learning models assisted by animation media and assisted by PPT media, 3) The effect of guided inquiry learning model assisted by animation media toward student learning outcomes. Type of research is Quasi Experiment with Nonequivalent Control Group design. The population was class VIII MTs YAPIT Malakaji. The sample was selected by purposive sampling. The instrument is 20 questions of learning outcomes test. Data analysis using descriptive and inferential analysis. The results showed: 1) The learning outcomes of students before implementation the guided inquiry learning model assisted by animation media were in the very low category with a score of 4.36, after which they were in the medium category with a score of 12.21, and assisted by PPT media were in the low category with a score of 5.07, after which they were in the low category with a score of 8.89. 2) Improvement of student learning outcomes using guided inquiry learning model assisted by animation media with N-Gain 0.50 medium category, assisted by PPT media with N-Gain 0.24 low category. 3) There is an effect of guided inquiry learning model assisted by animation media on students' learning outcomes.